2022
DOI: 10.1111/nuf.12812
|View full text |Cite
|
Sign up to set email alerts
|

Self‐care neglect through the voices of nurses working in primary healthcare clinics in Gauteng, South Africa

Abstract: Background Self‐care is essential, but while professional nurses often pay attention to the health of their patients, they give little heed to their own well‐being. With the current pandemic continuing to negatively affect the world, the need for health professionals to make time for self‐care is imperative. The concept “self‐care” is not a new phenomenon; however, this study strives to show the importance of self‐care practices in the world of nurses and its benefit for the nursing profession. The reality for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…The study conducted by Nkabinde-Thamae et al 16 further supports the significance of nurses' health awareness. Their research revealed that nurses unaware of changes in their health tended to neglect their self-care.…”
Section: Health Consciousnessmentioning
confidence: 71%
“…The study conducted by Nkabinde-Thamae et al 16 further supports the significance of nurses' health awareness. Their research revealed that nurses unaware of changes in their health tended to neglect their self-care.…”
Section: Health Consciousnessmentioning
confidence: 71%